Evaluasi Mine Dewatering System Untuk Menunjang Pencapaian Target Produksi 5.000 Ton/Shift Pada Penambangan Batubara Pit B Area Selatan PT. Mifa Bersaudara, Peunaga Cut Ujong, Meurebo, Kabupaten Aceh Barat, Provinsi Aceh - Novia Andiliani; Tamrin Kasim (Journals Mining Engineering : Bina Tambang, 2018)
PT. Mifa Bersaudara is a company engaged in the exploitation of coal using pit mining system. The mine of pit B PT. Mifa Bersaudara is located in Nagan Raya, Aceh provinces. The rains in the mining industry may affect mining operations, required a form optimal effort for handling incoming water to the mining area through a system of drainage mine engineering evaluated. The purpose of this study was to determine drainage system used specifically for the process of removing water that was at the sites. Calculation of rainfall plan determined using gumbel distribution, the calculation of rainfall during the 10 years plan is 716,32 mm/day. Rainfall intensity 103,9 mm/hours, flow codfficient of 0,9 and 0,3438 km2 catchment area (south). So that the results obtained discharge runoff into the sump (south) is 8,94 m3/second. Water in the sump (south) is pumped out of the pit by using two pumps is Multiflo 380 and Sykes HH 150. 386  m3/hours of actual discharge pump Multiflo 380 and pump Sykes HH 150 is 229 m3/hours. Multiflo 380 pump has 51,6 m of total head and Sykes HH 150 pump has 44,1 m. To resolve the water that will enter pit B is to let the water flow through the open channel and fit the sump. To accomodate the recharge water of 3971,7 m3 to the sump, it is recommended to construct a new sump with dimensions 218,67  m x 211,75 m x 6 m. Keywords:  Rain, Runoff, Catchment area, Sump, Pump.